1978
DOI: 10.1111/j.1471-4159.1978.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOSYNTHESIS OF S‐ADENOSYL‐L‐METHIONINE IN THE RAT PINEAL GLAND

Abstract: This investigation provides direct evidence that rat pineal gland contains ATP:L‐methionine S‐adenosyltransferase. The specific activity of the enzyme is about 25 times greater than that of hydroxyindole‐O‐methyltransferase, the unique marker enzyme in this tissue. The major product of the reaction catalyzed by ATP:L‐methionine S‐adenosyltransferase has been identified as S‐adenosyl‐methionine which can function as a methyl group donor for the formation of melatonin. The specific activity of pineal ATP:L‐methi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…With regard to the SAM level in the pineal gland, the literature includes results for other species: bovine (Baldessarini and Kopin, 1966) and human (Guchhait, 1976). In addition, investigations have provided direct evidence that rat pineal gland contains a high level of this nucleoside because of the high specific activity of the enzymatic system ATP-L-methionine-S-adenosyl-transferase (EC 2.5.1.6), which catalyses its formation (Guchhait and Gnau, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the SAM level in the pineal gland, the literature includes results for other species: bovine (Baldessarini and Kopin, 1966) and human (Guchhait, 1976). In addition, investigations have provided direct evidence that rat pineal gland contains a high level of this nucleoside because of the high specific activity of the enzymatic system ATP-L-methionine-S-adenosyl-transferase (EC 2.5.1.6), which catalyses its formation (Guchhait and Gnau, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…obtained from blank samples. Guchhait and Grau (1978), which uses ion-exchange chromatography for the isolation of the [I4C]SAM produced. The data obtained by the two methods ( Table 1) were in good agreement, but, in our experience, the method described in this report was much more practicable, allowing the simultaneous Identical tissue homogenates were assayed in duplicate.…”
Section: Resultsmentioning
confidence: 99%
“…MAT activity was found to be highest in the liver and low in the skeletal muscle; the enzyme was also detected in the CNS (Eloranta, 1979). Guchhait and Grau (1978) reported that the activity is much higher in the pineal gland than in a preparation from whole brain tissue. However the activity level in the pituitary gland and the distribution of the enzyme in various regions of the brain were not studied.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In the rat, the tissue distribution of methionine adenosyltransferase (MAT) and the differences in enzyme activity during brain maturation have been reported (Eloranta, 1977). MAT activity was much higher in the pineal gland than in the whole brain (Guchhait and Grau, 1978), and the distribution of enzyme activity in nine brain regions was found to be uniform (Hiemke and Ghraf, 1981).…”
mentioning
confidence: 87%